Upregulation of Calcium Homeostasis Modulators in Contractile-To-Proliferative Phenotypical Transition of Pulmonary Arterial Smooth Muscle Cells - Rodriguez, Marisela; Chen, Jiyuan; Jain, Pritesh P.; Babicheva, Aleksandra; Xiong, Mingmei; Li, Jifeng; Lai, Ning; Zhao, Tengteng; Hernandez, Moises; Balistrieri, Angela; Parmisano, Sophia; Simonson, Tatum; et al. (Frontiers in Physiology, 2021)
Excessive pulmonary artery (PA) smooth muscle cell (PASMC) proliferation and migration are implicated in the development of pathogenic pulmonary vascular remodeling characterized by concentric arterial wall thickening and arteriole muscularization in patients with pulmonary arterial hypertension (PAH). PASMC contractile-to-proliferative phenotypical transition is a process that promotes pulmonary vascular remodeling. A rise in cytosolic Ca2+ concentration ([Ca2+]cyt) in PASMCs is a trigger for pulmonary vasoconstriction and a stimulus for pulmonary vascular remodeling. Here, we report that the calcium homeostasis modulator (CALHM), a Ca2+ (and ATP) channel that is allosterically regulated by voltage and extracellular Ca2+, is upregulated during the PASMC contractile-to-proliferative phenotypical transition. Protein expression of CALHM1/2 in primary cultured PASMCs in media containing serum and growth factors (proliferative PASMC) was significantly greater than in freshly isolated PA (contractile PASMC) from the same rat. Upregulated CALHM1/2 in proliferative PASMCs were associated with an increased ratio of pAKT/AKT and pmTOR/mTOR and an increased expression of the cell proliferation marker PCNA, whereas serum starvation and rapamycin significantly downregulated CALHM1/2. Furthermore, CALHM1/2 were upregulated in freshly isolated PA from rats with monocrotaline (MCT)-induced PH and in primary cultured PASMC from patients with PAH in comparison to normal controls. Intraperitoneal injection of CGP 37157 (0.6 mg/kg, q8H), a non-selective blocker of CALHM channels, partially reversed established experimental PH. These data suggest that CALHM upregulation is involved in PASMC contractile-to-proliferative phenotypical transition. Ca2+ influx through upregulated CALHM1/2 may play an important role in the transition of sustained vasoconstriction to excessive vascular remodeling in PAH or precapillary PH. CALHM could potentially be a target to develop novel therapies for PAH.